Fuzzy Logic in Railway Vehicle Control – A Necessity or a Mode? - Lieskovsky, Ales; Myslivec, Ivo (Communications - Scientific letters of the University of Zilina, 2001)
The paper addresses features imputed by literature with real features of applied conventional (non-fuzzy) regulators for automation of railway vehicles control. It demonstrates with examples from everyday operation on the Czech Railways that conventional regulators are not only able for everyday operation, but they have parameters that fuzzy regulators will achieve only with difficulties. The authors support their assertions not by the results of simulations but by the results of real, long-term, everyday use of conventional speed regulators and target braking ones.